Observation of the high resolution infrared absorption spectrum of CO2 molecules isolated in solid parahydrogen: Low-Temperature Physics and Chemistry in Cryomatrice - Tam, Simon; Fajardo, Mario E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
We report the observation of high resolution (0.008 cm-1) infrared absorption spectra of CO2 molecules isolated in solid parahydrogen(pH2) matrices at T=2.4 to 4.8 K. Several extremely sharp (0.01 to 0.04 cm-1 full-width-at-half-maximum) absorption features appear in the 2343.5 to 2345 cm-1region. We assign the three strongest peaks to the n3 mode of isolated CO2 molecules. The spectra are consistent with trapping of the CO2 molecules in three distinct double-substitutional sites in hcp and fcc regions of the pH2 solid. We offer several hypotheses as to the origins of the numerous weaker absorption features.